Effects of seasonal climates and MIPS1 mutations on soybean germination through multi-omics analysis - Huakun Yu; Longming Zhu; Yuhao Chen; Ping Deng; Bei Liu; Xiaochao Chen; Fengjie Yuan (BMC Plant Biology)
Abstract This study delves into the combined effects of seasonal climate variations and MIPS1 gene mutations on the germination rates of soybean cultivars TW-1 and TW75. Through comprehensive metabolomic and transcriptomic analyses, we identified key KEGG pathways significantly affected by these factors, including starch and sucrose metabolism, lipid metabolism, and amino acid biosynthesis. These pathways were notably disrupted during the spring, leading to an imbalance in metabolic reserves critical for seedling development. Additionally, MIPS1 gene mutations further altered these pathways, exacerbating the metabolic disturbances. Our results underscore the intricate network of environmental and genetic interactions influencing soybean seed vigor and underscore the importance of understanding these pathways to enhance agricultural resilience and seed quality in fluctuating climates.